Empirical Evaluation of Visual Fatigue from Display Alignment Errors Using Cerebral Hemodynamic Responses. (24th December 2013) - Wiyor, Hanniebey D.; Ntuen, Celestine A.
Abstract : The purpose of this study was to investigate the effect of stereoscopic display alignment errors on visual fatigue and prefrontal cortical tissue hemodynamic responses. We collected hemodynamic data and perceptual ratings of visual fatigue while participants performed visual display tasks on 8 ft× 6 ft NEC LT silver screen with NEC LT 245 DLP projectors. There was statistical significant difference between subjective measures of visual fatigue before air traffic control task (BATC) and after air traffic control task (ATC 3), (P < 0.05 ). Statistical significance was observed between left dorsolateral prefrontal cortex oxygenated hemoglobin ( l DLPFC-HbO2 ), left dorsolateral prefrontal cortex deoxygenated hemoglobin ( l DLPFC-Hbb), and right dorsolateral prefrontal cortex deoxygenated hemoglobin ( r DLPFC-Hbb) on stereoscopic alignment errors (P < 0.05 ). Thus, cortical tissue oxygenation requirement in the left hemisphere indicates that the effect of visual fatigue is more pronounced in the left dorsolateral prefrontal cortex.